2020
DOI: 10.1177/0963689720919435
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA ZFAS1 Promotes Progression of NSCLC via Regulating of miR-590-3p

Abstract: The incidence and mortality rate of nonsmall cell lung cancer (NSCLC) are continuously increasing. Recently, the important roles of long noncoding ribonucleic acid (lncRNA) zinc finger antisense1 (ZFAS1) in the development of many disease have been proved. However, the roles of ZFAS1 in NSCLC are still not completely understood. Thus, this study aimed to explore the potential roles and underlying mechanisms of lncRNA ZFAS1 in the progression of NSCLC. Our results demonstrated that lncRNA ZFAS1 expression was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Here, we revealed that levels of CFHR3 were negatively and significantly associated with miR-590-3p levels in HCC tissues. Several studies show that miR-590-3p is a decisive prognostic marker for cancers, including HCC, colorectal cancer, and non-small cell lung cancer [ 28 30 ]. In our further study, the inhibition of CFHR3 mRNA levels by miR-590-3p was figured out.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we revealed that levels of CFHR3 were negatively and significantly associated with miR-590-3p levels in HCC tissues. Several studies show that miR-590-3p is a decisive prognostic marker for cancers, including HCC, colorectal cancer, and non-small cell lung cancer [ 28 30 ]. In our further study, the inhibition of CFHR3 mRNA levels by miR-590-3p was figured out.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that lncRNA ZFAS1 inhibits mitotic cycle 42 expression through regulating miR-590-3p in NSCLC cells [35]. Moreover, several studies have shown that has-miR-590-3p is involved in tumor development in several cancers, including ovarian cancers, colorectal cancer, and renal clear cancer [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers and scholars have studied the mechanism: lncRNA MAGI2-AS3 inhibits the proliferation, migration and invasion of NSCLC cells by regulating miR-374a/b-5p/CADM2, miRNA-23a-3p/PTEN and miR-629-5p/TXNIP axis and up-regulating RECK and cytokine signaling 1 in combination with miR-25 and miR-15583 (Hao and Yang 2019 ; He et al 2020 ; Li et al 2020 ). However, the lncRNA ZFAS1, which regulates NSCLC cell proliferation through ZFAS1/miR-590-3p axis, was found to be downregulated in TEPs of NSCLC patients (Luo et al 2018 ; Zhou et al 2020 ). This may be influenced by factors from different gene sources, and the same gene may exhibit different expression trends in pathological tissues and TEPs.…”
Section: Clinical Application Of Tepsmentioning
confidence: 99%